Cultural intelligence (CQ) and expatriation intention / Nur Aliea Mohd Nazori - Mohd Nazori, Nur Aliea (Faculty of Business and Management, 2018)
This study examines on Cultural Intelligence CQ and Expatriation Intention. The results were collected from 130 numbers of respondents through a questionnaires. A survey consisting of 24 questions that uses a Likert Scale questions to establishing measurable values from the respondents. The data analysis intends to determine whether there are significant effect between the independent variables (Cognitive CQ, Metacognitive CQ, Motivational CQ and Behavioural CQ) with the dependent variable (Expatriation Intention). This study found that there were only three from the independent variables (Cognitive CQ, Metacognitive and Motivational CQ) has significant effect where by only one independent variable (Behavioural CQ) has insignificant effect with the dependent variable (Expatriation Intention). The data has been analyzed by using SPSS software.